Une tout autre forme d’authenticité. Travail du désir et anthropologie de la médiation chez Simone Weil - Simeoni, Francesca (Labyrinth, 2023)
The aim of this article is to examine the actuality of Simone Weil's concept of the impersonal, as expressed in La personne et le sacré. To this end, I address the theme of authenticity by proposing two alternative models. According to the first model, "being oneself" corresponds to the immediate self-expression. Weil's critique of the "person's right to self-fulfillment", on the other hand, gives rise to an anthropology of mediation, which constitutes a second model centered on the notion of work. Hence, my original contribution consists in the argumentation of the thesis that in Weil's oeuvre the access to the self is structured in concordance to a "work of desire", which constitutes the human being's essence. Taking up the various allusions to the "desire for the good", scattered throughout the Weilian corpus, the article unveils what this affective work, that transforms the subject, consists of, and emphasizes the importance of the experience of the transcendent Good as a condition for a free interpretation of the value of the desired goods.